Using Spice Circuit Simulation Program in Reliability Analysis of Redundant Systems with Non-Repairable Units and Common-Cause Failures - Muhammad Taher Abuelma'atti; Isa Salman Qamber (Active and Passive Electronic Components)
The effectiveness of Simulation Program with Integrated Circuit Emphasis (SPICE) in calculating probabilities, reliability, steady-state availability and mean-time to failure of redundant systems with non-repairable units and common-cause failures described by Markov models is demonstrated. General equations and procedure for constructing the equivalent circuit for N parallel units are presented. Results obtained, for N=1,2,3, using SPICE are compared with previously published results obtained using the Laplace transform method. Full SPICE listings are included.